2023
DOI: 10.3389/fimmu.2023.1117092
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 promotes self-renewal of progenitor exhausted CD8 T cells during persistent antigenic stimulation

Abstract: In chronic infections and cancer, exhausted CD8 T cells exhibit heterogeneous subpopulations. TCF1+PD-1+ progenitor exhausted CD8 T cells (Tpex) can self-renew and give rise to Tim-3+PD-1+ terminally differentiated CD8 T cells that retain their effector functions. Tpex cells are thus essential to maintaining a pool of antigen-specific CD8 T cells during persistent antigenic stimulation, and only they respond to PD-1-targeted therapy. Despite their potential as a crucial therapeutic target for immune interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Similar to memory CD8 + T cells 42 , we recently reported that the TCF1 + progenitor exhausted CD8 + T cell subset exclusively self-renewed after ex vivo and in vivo IL-15 stimulation in chronically LCMV-infected mice and patients with metastatic renal cell carcinoma 43 . We first observed that only TCF1 - CD8 + T cells showed minimal CD122 (IL-2/15Rβ) expression, while both subsets exhibited considerable expression of CD132 (common ɣ chain receptor) at 28 days post allogeneic transplantation (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Similar to memory CD8 + T cells 42 , we recently reported that the TCF1 + progenitor exhausted CD8 + T cell subset exclusively self-renewed after ex vivo and in vivo IL-15 stimulation in chronically LCMV-infected mice and patients with metastatic renal cell carcinoma 43 . We first observed that only TCF1 - CD8 + T cells showed minimal CD122 (IL-2/15Rβ) expression, while both subsets exhibited considerable expression of CD132 (common ɣ chain receptor) at 28 days post allogeneic transplantation (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…IL-15 reinvigorated tumor-infiltrating CD28 - PD-1 + CD8 + T cells that are unresponsive to PD-1 blockade in non-small cell lung cancer (NSCLC) ( 111 ). IL-15 also plays a crucial role in the self-renewal of progenitor exhausted TCF-1 + PD-1 + CD8 + T cells, which are characterized by stem-like properties and associated with a more favorable response to PD-1 blockade ( 112 ).…”
Section: Il-15 Promotes Cd8 + T Cell-mediated Anti...mentioning
confidence: 99%
“…This cytokine plays a crucial role in promoting the proliferation of CD8 + T cells, and its absence in the TME has been associated with impaired function of CD8 + T cells, tumor relapse, and diminished patient survival 83 , 84 . Previous studies have demonstrated that co-culturing CD8 + TILs derived from human renal cell carcinoma with IL-15 enhances the self-renewal capability of these cells 85 .…”
Section: Application Of Tpex Cells In Tumor Immunotherapymentioning
confidence: 99%